1988
DOI: 10.1128/aac.32.9.1354
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to hydrophobic molecules and phospholipid composition in Pasteurella multocida and Actinobacillus lignieresii

Abstract: Despite its typically gram-negative cell envelope ultrastructure, Pasteurella multocida is susceptible to the hydrophobic antibiotic novobiocin and is unable to initiate growth on MacConkey agar, a parameter often used to effect its differentiation from other members of the family Pasteurellaceae such as Actinobacillus lignieresii. However, growth on basal medium supplemented with individual selective factors and an agar diffusion assay revealed the bile salts contained in MacConkey agar to be toxic to both or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…This agrees with former investigations [13]. It is remarkable that there are no differences between the examined species.…”
Section: Phospholipidssupporting
confidence: 82%
See 1 more Smart Citation
“…This agrees with former investigations [13]. It is remarkable that there are no differences between the examined species.…”
Section: Phospholipidssupporting
confidence: 82%
“…So far only limited experience has been accumulated as to the taxonomic significance of phospholipid composition [13,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, the kcat values were consistently 10-fold higher for substrate within membranes than for purified substrate when purified PilD was used, while the k5t value To determine whether phospholipids from bacterial membranes could provide a better medium for the cleavage reaction, the relative rates of cleavage of prepilin were determined in the presence of such phospholipids. Total phospholipids were extracted by methanol-chloroform extraction from Escherichia coli DH5ot and the pilA pilD double mutant P. aeruginosa B30-NP by established procedures (17) to determine their ability to substitute for crude membranes in the PilD in vitro assay. These results are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effect of triclosan and methyl triclosan on the ability to initiate growth was determined using a modification of a standardized disk agar diffusion bioassay (Hart and Champlin, 1988 …”
Section: Disk Agar Diffusion Bioassaymentioning
confidence: 99%
“…Enhanced uptake of the hydrophobic probe 1-N-phenylnaphthylamine relative to the refractory control organisms P. aeruginosa and Escherichia coli suggested the presence of regions of surface-exposed phospholipid bilayer in the P. multocida outer membrane. It was concluded that the extreme susceptibility of P. multocida to triclosan (Champlin et al, 2005) as well as other nonpolar antimicrobial agents (Hart and Champlin, 1988) is due to the general inability of the outer membrane to exclude hydrophobic molecules. Low triclosan concentrations which inhibited growth of untreated P. multocida cultures were only effective for P. aeruginosa when rendered susceptible using outer membrane-permeabilizing concentrations of polymyxin Bnonapeptide, compound 48/80, or ethylenediaminetetraacetate (Champlin et al, 2005).…”
mentioning
confidence: 99%